2021
DOI: 10.1007/s12155-021-10280-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Torrefaction of Sunflower Husk Pellets in the Kaolin Layer

Abstract: In this paper oxidative torrefaction of sunflower husk pellets in the kaolin layer was firstly investigated. Besides, influence of kaolin without use of special additives on limitation of the oxygen flow from environment into the sunflower husk was analyzed. Torrefaction temperature, torrefaction time, and height of kaolin layer over the range of 240-280 °C, 30-60 min, and 3-5 cm, respectively were varied. Analysis showed that increase of temperature led to more significant influence of layer height on mass yi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…As a guideline, it is observed that the density of the pellets for a moisture content of 10% of 1100 g/cm 3 will decrease for a moisture content of 0% to about 0.909 g/cm 3 , i.e., 909 kg/m 3 . The difference in value determined the decision that the moisture of the pellets must be taken into consideration during the research [53][54][55][56][57]. The dependence relationship (7) can be used in another way by finding the density at a certain moisture content, thus finding the following general relationship (Equation ( 9)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a guideline, it is observed that the density of the pellets for a moisture content of 10% of 1100 g/cm 3 will decrease for a moisture content of 0% to about 0.909 g/cm 3 , i.e., 909 kg/m 3 . The difference in value determined the decision that the moisture of the pellets must be taken into consideration during the research [53][54][55][56][57]. The dependence relationship (7) can be used in another way by finding the density at a certain moisture content, thus finding the following general relationship (Equation ( 9)).…”
Section: Methodsmentioning
confidence: 99%
“…The higher the ash content, the lower the calorific value of the pellets. When analyzing wood pellets with an ash content of less than 1%, there is no question of the influence of the ash content on the calorific value, but this problem is particularly important for some tropical species with an ash content of 2.5%-3.5% [3,47,57] or for pellets of some agricultural products (beans or peas) that have an ash content of over 20% [3,4,10]. In order to model the influence of the ash content on the calorific value of the pellets, the chemical elements of wood, namely carbon, hydrogen, oxygen and ash, the participation percentage and the calorific value of these components were taken into account, according to the following calculation reaction of Channiwala and Parikh [1,3,49] (Equation ( 13 where CV-the calorific value of materials, in MJ/kg; 33.910, 11.783, 1.034 and 0.211 are the calorific values of the carbon, hydrogen, oxygen and ash content, in MJ/kg; C-the carbon content of the pellets, in %; H-the hydrogen content, in %; O-the oxygen content of the pellets, in %; Ac-the ash content of the pellets, in %.…”
Section: Calorific Value Modeling Depending On the Ash And Carbon Con...mentioning
confidence: 99%